2007
DOI: 10.2478/v10003-007-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Age of Black Coloured Laminae Within Speleothems from Domica Cave and Its Significance for Dating of Prehistoric Human Settlement

Abstract: Abstract:The paper deals with the black coloured laminae which occur within speleothems in Domica cave (Slovakia). The laminae are composed of non completely carbonized organic compounds and charcoal particles. The components were formed during combustion of plant material, mainly wood, inside the cave. Thus, they are a by-product of human activity inside the cave. The radiocarbon ages of organic fraction of these laminae fall between 6460 and 6640 cal BP and 7160 and 7330 cal BP. These dates indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…Thus, the analysis of this geological object offers insight into the behavior of past societies. Few studies have investigated such material (see for example Benington et al, 1962;Genty et al, 1997bGenty et al, , 1998Delannoy et al, 2009) and the issues of the micro-chronology of site occupation (Genty et al, 1997b;Verheyden et al, 2006), and the link between archaeological deposits and speleothems (Petr anek and Pouba, 1951;Gradzi oski et al, 2001;Gradzi nski et al, 2007;Martínez-Pillado et al, 2010, 2014, though sometimes discussed, are never considered together. Previous investigations have suggested that soot deposits are a very good marker of human presence (Gradzi oski et al, 2001;Gradzi nski et al, 2003;Martínez-Pillado et al, 2010, 2014 and may be directly dated to identify periods of attendance at a site (Petr anek and Pouba, 1951;Benington et al, 1962;Gradzi oski et al, 2001;Gradzi nski et al, 2003Gradzi nski et al, , 2007, though none have investigated the utility of these markers as a tool for micro-chronological studies of site occupation and linked the occupation sequences reconstructed with the associated archaeological level.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the analysis of this geological object offers insight into the behavior of past societies. Few studies have investigated such material (see for example Benington et al, 1962;Genty et al, 1997bGenty et al, , 1998Delannoy et al, 2009) and the issues of the micro-chronology of site occupation (Genty et al, 1997b;Verheyden et al, 2006), and the link between archaeological deposits and speleothems (Petr anek and Pouba, 1951;Gradzi oski et al, 2001;Gradzi nski et al, 2007;Martínez-Pillado et al, 2010, 2014, though sometimes discussed, are never considered together. Previous investigations have suggested that soot deposits are a very good marker of human presence (Gradzi oski et al, 2001;Gradzi nski et al, 2003;Martínez-Pillado et al, 2010, 2014 and may be directly dated to identify periods of attendance at a site (Petr anek and Pouba, 1951;Benington et al, 1962;Gradzi oski et al, 2001;Gradzi nski et al, 2003Gradzi nski et al, , 2007, though none have investigated the utility of these markers as a tool for micro-chronological studies of site occupation and linked the occupation sequences reconstructed with the associated archaeological level.…”
Section: Introductionmentioning
confidence: 99%
“…Individual layer is 40 μm thick, whereas the whole rim is up to 400 μm. Their thickness is comparable to those black layers attributed to urban aerosols from South Korean tourist caves (Chang et al 2007), where pollutants are concentrated at the surface of the speleothems, and 0.1 to several millimetres thick and, more important, to laminae interpreted as result of combustion of plant material within several caves (Gradziński et al 2007).…”
Section: Resultsmentioning
confidence: 61%
“…The ultra structures of charcoal particles prove that most originated in temperatures ranging from 400 up to 600 °C, suggesting that charcoal is connected with domestic fires rather than torches (Gradziński et al 2003). The occurrence of laminae within flowstones close to the cave entrance shows that components of tracing dyes could be transported into the cave by wind action (Gradziński et al 2007). As in Črna Jama no other evidence indicates human inhabitation of the place, charcoal occurrence could not be unambiguously explained.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to artefacts (ceramics, bone and stone tools), these people left a special print in the cave, as many dripstones were coloured to grey or black from the torches and fires they used. However, when they left the cave, it remained uninhabited for several millennia and thus younger speleothem layers coated these dark layers (Gradziński et al 2007).…”
Section: The Baradla-domica Cave Systemmentioning
confidence: 99%